Agricultural economics - Drummond, H. Evan (Prentice Hall, 2001)
For one-semester, introductory courses in Agricultural Economics or Environmental Economics. This innovative text provides a broad view of the food system, with its emphasis on the links among financial institutions, the macroeconomy, world markets, government programs, farms, agribusinesses, food marketing, and the environment. Taking a macro-to-micro approach, the text introduces "high interest" topics students can relate to first, using them to capture student interest before introducing microeconomics topics. It illustrates the six economic concepts which form the foundation of the economist's decision-making process including supply and demand, opportunity cost, diminishing returns, marginality, measuring costs and returns, and the externalities of transactions. Presented in a non-threatening conceptual framework, the material covered in this text maintains a strong attachment to the application of agricultural economics to the real world.